Capability factors in changing patterns of international knowledge relationships among university spin-off firms in Northwest Europe - Marina Van Geenhuizen (European Regional Science Association (ERSA), 2016)
Industrial competence is increasingly dispersed across the globe, urging technology-based firms in Europe to establish international knowledge relationships at larger distances. This paper examines changing patterns of international knowledge relationships and the influence of capability factors of university spin-off firms on building such relationships, using a sample of 105 of such firms. The paper addresses the debate on capabilities among young high-tech ventures in developing an adequate internationalization network, in which opinions are contrasting, like concerning an easy globalization (born-global model) versus a reluctant and step-wise approach. In early patterns, 62 per cent of the sampled firms employed knowledge relationships abroad. The main capability factors affecting these early relationships tend to be PhD education in the founding team, participation in training, and the capability to innovate on a practical and modestly innovative level responding to market demand. The subsequent changes in relationships have led to a high overall internationalization level of 82 per cent five years later, but also reveal diverse trends on the individual level of firms, namely, no change for half of the spin-offs but an increase of spatial reach for only one third. With the aim to explore spatial internationalization patterns and changes herein, we apply logistic regression analysis. Important factors affecting both early and later international networks tend to be entrepreneurial orientation, regarding industry sector and market, while later relationships tend to be path-dependent, i.e. mainly influenced by the previous pattern.
Keywords: D8; L21; L26; M13; 330; University spin-off firms; Knowledge relationships; Spatial reach; Capability factors